CRF1 Receptor‐Dependent Increases in Irritability‐Like Behavior During Abstinence from Chronic Intermittent Ethanol Vapor Exposure. (22nd September 2017) - Kimbrough, Adam; de Guglielmo, Giordano; Kononoff, Jenni; Kallupi, Marsida; Zorrilla, Eric P.; George, Olivier
Abstract : Background: In humans, emotional and physical signs of withdrawal from ethanol are commonly seen. Many of these symptoms, including anxiety‐like and depression‐like behavior, have been characterized in animal models of ethanol dependence. One issue with several current behavioral tests that measure withdrawal in animal models is that they are often not repeatable within subjects over time. Additionally, irritability, one of the most common symptoms of ethanol withdrawal in humans, has not been well characterized in animal models. The corticotropin‐releasing factor (CRF)‐CRF1 receptor system has been suggested to be critical for the emergence of anxiety‐like behavior in ethanol dependence, but the role of this system in irritability‐like behavior has not been characterized. Methods: The present study compared the effects of chronic intermittent ethanol (CIE) vapor exposure‐induced ethanol dependence on irritability‐like behavior in rats using the bottle‐brush test during acute withdrawal and protracted abstinence. Rats were trained to self‐administer ethanol in operant chambers and then either left in a nondependent state or made dependent via CIE. Naïve, nondependent, and dependent rats were tested for irritability‐like behavior in the bottle‐brush test 8 hours and 2 weeks into abstinence from ethanol. Separate cohorts of dependent and nondependent rats were used to examine the effect of the specific CRF1 receptor antagonist R121919 on irritability‐like behavior. Results: Dependent rats exhibited escalated ethanol intake compared with their own pre‐CIE baseline and nondependent rats. At both time points of abstinence, ethanol‐dependent rats exhibited increased aggressive‐like responses compared with naïve and nondependent rats. R121919 reduced irritability‐like behavior in both dependent and nondependent rats, but dependent rats were more sensitive to R121919. Conclusions: Irritability‐like behavior is a clinically relevant and reliable measure of negative emotional states that is partially mediated by activation of the CRF‐CRF1 system and remains elevated during protracted abstinence in ethanol‐dependent rats. Abstract : A common ethanol (EtOH) withdrawal symptom in humans is irritability, which has been difficult to characterize in animal models of EtOH addiction. This study used an animal model of EtOH dependence and found aggressive irritability‐like behavior increased during withdrawal and protracted abstinence. CRF1 receptor blockade reduced irritabilitylike behavior in EtOH‐dependent and nondependent rats, suggesting the CRF‐CRF1 system may mediate irritability‐like behavior. The use of the bottle‐brush test to measure irritability may be highly relevant to addiction for multiple drugs of abuse.